Motor Unit Number Estimation in Infants and Children with Spinal Muscular Atrophy - Bromberg, Mark B. (Muscle Nerve, 2002)
Spinal muscular atrophy (SMA) is a disease of lower motor neurons. Motor unit number estimation (MUNE) is an electrophysiologic method to estimate the number of motor neurons innervating a muscle group. We applied the multiple point stimulation technique to the ulnar nerve–hypothenar muscle group to study lower motor neuron loss in 14 SMA subjects, including those presymptomatic, and varying from newborn through 45 years of age. Preliminary data support the value of MUNE to help understand the time course of motor neuron loss in SMA.